2015
DOI: 10.1016/j.biocon.2014.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the hidden niches of cryptic bumblebees in Great Britain: Implications for conservation

Abstract: a b s t r a c tBumblebees are ecologically and economically important, and some species have suffered dramatic population declines. The absence of morphological diagnostic characters for the identification of some species creates difficulties for basic ecological studies, and for conservation management. The widespread and commercially exploited bumblebee subgenus Bombus sensu stricto contains a cryptic species complex, known as the lucorum complex, which in Europe comprises B. lucorum, B. cryptarum and B. mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 48 publications
6
38
0
Order By: Relevance
“…Roberts et al (2011) demonstrated that three generalists and three specialist species of Colletes might be threatened by climate change, and for the global bee diversity hotspot of the GCFR, substantial range contraction for most bee species under a scenario of warming climate is predicted (Kuhlmann et al 2012). In our study, the significant association of a number of climatic variables (precipitation of the wettest month, irradiance of the warmest quarter and growing degree days) with species richness estimates corroborates the results of the earlier studies and suggests that changing climate might have a direct effect on bee diversity at the global to regional scales (Williams et al 2009;Pradervand et al 2014;Scriven et al 2015). Further, the directionality and relative importance of various climatic variables appears to be consistent across different scales and geographic regions; however area-specific differences cannot be ruled out.…”
Section: Discussionsupporting
confidence: 91%
“…Roberts et al (2011) demonstrated that three generalists and three specialist species of Colletes might be threatened by climate change, and for the global bee diversity hotspot of the GCFR, substantial range contraction for most bee species under a scenario of warming climate is predicted (Kuhlmann et al 2012). In our study, the significant association of a number of climatic variables (precipitation of the wettest month, irradiance of the warmest quarter and growing degree days) with species richness estimates corroborates the results of the earlier studies and suggests that changing climate might have a direct effect on bee diversity at the global to regional scales (Williams et al 2009;Pradervand et al 2014;Scriven et al 2015). Further, the directionality and relative importance of various climatic variables appears to be consistent across different scales and geographic regions; however area-specific differences cannot be ruled out.…”
Section: Discussionsupporting
confidence: 91%
“…All three species co‐occur at many locations in Great Britain and Ireland; additionally, Scriven et al. (), Murray et al. (), and Stanley et al.…”
Section: Introductionmentioning
confidence: 99%
“…; Scriven et al. ). All three species co‐occur at many locations in Great Britain and Ireland; additionally, Scriven et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations